2023
DOI: 10.1177/0044118x231179245
|View full text |Cite
|
Sign up to set email alerts
|

Growing Up in Adversity: A Moderated Mediation Model of Family Conflict, Cyberbullying Perpetration, Making Sense of Adversity and Depression

Chaoxin Jiang,
Shan Jiang

Abstract: Although family conflict is recognized as a detrimental factor for adolescents’ depression, the underlying mechanisms remain unknown. This study investigates the mediating effect of cyberbullying perpetration and the moderating effect of making sense of adversity in this association. A sample of 814 Chinese adolescents (Mean age = 16.79 years) from Zhejiang province, China, is collected through multi-stage cluster random sampling. The moderated mediation model is performed by SPSS macro PROCESS. The results il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(145 reference statements)
0
1
0
Order By: Relevance
“…Studies among Chinese participants (including Hong Kong) have found that children who have experienced poverty show greater resilience, more positive beliefs and behaviors in the face of adversity ( 39 , 40 ). Furthermore, in Chinese family, virtues of harmony and endurance are underscored, which would help children cope with family conflict ( 41 , 42 ). Research suggests that balanced sibling relationships, including both conflict and support, are associated with the better social-emotional skills.…”
Section: Discussionmentioning
confidence: 99%
“…Studies among Chinese participants (including Hong Kong) have found that children who have experienced poverty show greater resilience, more positive beliefs and behaviors in the face of adversity ( 39 , 40 ). Furthermore, in Chinese family, virtues of harmony and endurance are underscored, which would help children cope with family conflict ( 41 , 42 ). Research suggests that balanced sibling relationships, including both conflict and support, are associated with the better social-emotional skills.…”
Section: Discussionmentioning
confidence: 99%